2018
DOI: 10.1016/j.jtho.2017.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nivolumab versus Docetaxel on Health-Related Quality of Life and Symptoms in Patients with Advanced Squamous Non–Small Cell Lung Cancer: Results from the CheckMate 017 Study

Abstract: Nivolumab alleviates symptom burden and improves health status versus docetaxel as second-line squamous NSCLC treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
85
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 29 publications
6
85
0
3
Order By: Relevance
“…The pivotal phase III CheckMate 017 7 and 057 6 randomized clinical trials demonstrated a significantly improved OS benefit with nivolumab over docetaxel among these patients, with a significant improvement in health-related quality of life (HRQoL). 11,12 To date, there have been few large-scale prospective realworld studies reporting the effectiveness and safety of nivolumab treatment in advanced NSCLC patients in Europe. The major strength of a prospective cohort study is the accuracy of data collection with regard to exposures, confounders and endpoints.…”
Section: Introductionmentioning
confidence: 99%
“…The pivotal phase III CheckMate 017 7 and 057 6 randomized clinical trials demonstrated a significantly improved OS benefit with nivolumab over docetaxel among these patients, with a significant improvement in health-related quality of life (HRQoL). 11,12 To date, there have been few large-scale prospective realworld studies reporting the effectiveness and safety of nivolumab treatment in advanced NSCLC patients in Europe. The major strength of a prospective cohort study is the accuracy of data collection with regard to exposures, confounders and endpoints.…”
Section: Introductionmentioning
confidence: 99%
“…Some clinical trials of ICMs have collected PRO data, and there are several reports published regarding their impact on HRQOL . Although the use of general PRO tools to measure HRQOL in patients treated with ICMs on a clinical trial is a reasonable strategy in the absence of more specific tools, there are limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical trials of ICMs have collected PRO data, and there are several reports published regarding their impact on HRQOL. [3][4][5][6][7][8][9][10][11] Although the use of general PRO tools to measure HRQOL in patients treated Nivolumab 15 10 Ipilimumab 13 9 Pembrolizumab 13 9 Atezolizumab 11 7 Tremelimumab 11 8 Durvalumab 10 7 Avelumab 7 4 Other 4 3 Abbreviations: CNS, central nervous system; ICM, immune checkpoint modulator.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations